As conferências nacionais de política para as mulheres e os sentidos atribuídos á deliberação - Silva, Maria Camila Florêncio da (2014)
This dissertation seeks to understand the normative profile of the Woman Policy National Conference through the meanings attributed to deliberation by the governmental and nongovernmental representatives who organized and/or participated to proceedings of the Conferences. The relevance of the problem is caused by the diagnosis that the profile of these conferences, marked by historical discourses that seek to establish the political commitment of the federal government with the policy for women, it is not clear to anyone who participates. Despite this, it is also justified by the discussions around proposals Participation Systems that seek to work with the complementarity of models of democracy. In the theoretical framework, lies the notion of 'deliberative moments' present in the Brazilian literature of participation effectiveness and the juridic notions of discretionary and binding administrative act on the field of Administrative Law as attempts to understand consultives analytical and deliberatives categories on brazilian literatura of participation. These categories, however,are limited to understand the several meanings of deliberation that would indicates its profile.